Topological Materials in Heusler Compounds - Sun, Yan; Felser, Claudia (Springer Science and Business Media Deutschland GmbH, 2018)
As a class of tuneable materials, Heusler has grown into a family of more than 1000 compounds, synthesized from combinations of more than 40 elements. Recently, by incorporating heavy elements that can give rise to strong spin–orbit coupling (SOC), non-trivial topological phases of matter, such as topological insulators (TIs), have been discovered in Heusler materials. The interplay of symmetry, SOC and magnetic structure allows for the realization of a wide variety of topological phases through Berry curvature design. Weyl points and nodal lines can be manipulated by various external perturbations, which results in exotic properties such as the chiral anomaly, large anomalous, spin and topological Hall effects. The combination of a non-collinear magnetic structure and Berry curvature gives rise to a nonzero anomalous Hall effect, which was first observed in the antiferromagnets Mn:3 Sn and Mn:3 Ge. Besides this k-space Berry curvature, Heusler compounds with non-collinear magnetic structures also possess real-space topological states in the form of magnetic antiskyrmions, which have not yet been observed in other materials.
CRIS-Team Scopus Importer:2022-04-14